2008
DOI: 10.1097/inf.0b013e3181694fb9
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of Viral Coinfection in Children Hospitalized With Acute Respiratory Tract Infection Using a Real-Time Polymerase Chain Reaction

Abstract: Simultaneous testing of respiratory viruses by real-time PCR is a suitable tool for the detection of viral coinfections. In children hospitalized because of respiratory infection viral coinfection is frequently detected with RSV and hBoV being a common combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
130
10
22

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(183 citation statements)
references
References 30 publications
21
130
10
22
Order By: Relevance
“…In contrast to previous reports (Calvo et al 2007, 2008, Cheuk et al 2007, Bonzel et al 2008, we observed that HRV-PIV co-infection (median of 1.5 m.o.) was more …”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to previous reports (Calvo et al 2007, 2008, Cheuk et al 2007, Bonzel et al 2008, we observed that HRV-PIV co-infection (median of 1.5 m.o.) was more …”
Section: Discussioncontrasting
confidence: 56%
“…Diagnosis of acute respiratory tract infection (ARI) and discrimination between bacterial and viral infection is not straight-forward. The diagnosis, clinical management, and understanding of the pathogenesis of a child presenting with symptoms of viral infection can be readily improved by using multiplex PCR to determine the presence or absence of a viral respiratory pathogen (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Además de la mayor sensibilidad para la detección etiológica de virus respiratorios tradicionales y del mayor número de agentes virales identificados, los ensayos PRM-RPC han mejorado la en relación al inicio de los síntomas 2,7 . La velocidad de implementación de técnicas de biología molecular en laboratorios de virología no ha sido muy rápida, considerando los costos directos e indirectos que se requieren 13 .…”
Section: Comentariosunclassified
“…Además, las IRA son la primera causa de consultas ambulatorias y hospitalizaciones, así como también una importante causa de ausentismo escolar y laboral 6 . Si bien los virus son los agentes que con mayor frecuencia producen IRA a todas las edades, comparativamente son más comunes en niños que en adultos y causan cuadros más graves en grupos de riesgo, como menores de 2 años, ancianos, inmunosuprimidos y pacientes con comorbilidades 4,7 . En estos pacientes es fundamental encontrar técnicas diagnósticas rápidas, sensibles y precisas, especialmente en el estudio de infecciones respiratorias bajas 8 .…”
unclassified
See 1 more Smart Citation